Women Empowerment: The Role of Education in Women Empowerment - Dr. Kunhi Sikha Bhuyan (International Journal of Advanced Science and Technology, 2020)
“Empowerment of women” is a topic that has been debated and deliberated world over. The half of the population of the world is women, they reach in the top of the sky but till we are taking about women empowerment. Empowerment of women means equipping them to be self reliant, confident and economically independent with a positive self-esteem, ability to take decisions to participate in developmental process and social change. According to Asian and Pacific Centre for Women and Development defines empowerment as a process that aims at creating the conditions for the self-determination of a particular people or group. Gender inequality is very common not only in our society but also it’s a major challenge in front of the world community. Education is a fundamental right for all people, women and men throughout the world. Every person is benefited with educational opportunities which are designed to meet the needs of the life. To empower women education can plays a very important role, education is empowerment. India still has one of the lowest female literacy rates; low level of literacy has negative impact on women’s lives and also on their family and the economic and social development of our country. In here we are discussing about women empowerment through education; the problems, the historical background of women education, constitutional provision and also forwarded some suggestions. Hope that our paper will help about to understanding the women educational scenario and importance of education in her development and empowerment.